Report on the Assessment of Thermal Insulator for RFoF Optical Link Cable - Juswardy, Budi (2019)
This report documents the selection process, characterisation and analysis of insulating solutions for surface-laid fibre optic cable from outdoor elements (ambient temperature fluctuations, wind and solar irradiation) in the field at the Murchison Radio-astronomy Observatory (MRO), in the context of SKA Bridging Array activity. The objective of the investigation is to find a solution that potentially mimic the response of underground cable burial (1.5 m) in reducing thermal effect on the fibre cable, to achieve reasonable phase stability of the transmitted RF signal, without actually trenching the cable. Worst-case estimates of the relative phase variation and the 24-hour relative phase drift of the installation (with and without the insulator) are provided, which are derived from actual cable measurements in the field, as well as calculated from characterisations of insulation sample in the lab. These estimates can then be used to predict the performance of future fibre cable installations for any given length, and to make an informed decision whether or not trenching the cable underground/ cable insulation is required, or weather cable performance is acceptable without any insulation. For SKA Bridging Array station with 200 m length fibre transmission distance, the worst-case estimate for the 24-hour relative RF phase drift between two RF links at 160 MHz would be in the order of: 1.5° (phase) for surface laid cable without insulation. Depending on the thickness of the insulator as evaluated, the relative phase drift is calculated to potentially be reduced down to approximately: 0.9° - 0.45° (phase) for insulator thickness between 25 mm – 75 mm, and the 50 mm wall thickness is found to be capable of providing damping and delayed temperature response, similar to the profile of cable buried 1.5 m underground.